The impact of former iron ore mining on the transformation of vegetation cover of the Gielniowski Hump (Małopolska Upland) - Podgórska, Monika (Biodiversity: Research and Conservation, 2011)
The impact of the 17th-19th century iron ore mining on the current state of vegetation cover of the Gielniowski Hump, an upland region situated within the Old Polish Industrial Region (a former centre of mining and smelting), was studied. In the course of the research, the detailed floristic lists were compiled using the cartogram method (ATPOL grid) and phytosociological relevés were made according to the Braun-Blanquet method. Relevés were taken both at the post-mining sites (on spoil banks) and, for comparative purposes, in the adjacent, not affected areas. The obtained results show significant differences between the flora and vegetation of the sites affected and unaffected by mining. These differences result from the changed mineralogical composition of soil in the post-mining areas, which has lead to an increase in the proportion of mesophilous forest communities and in the number of species of the class Querco-Fagetea as compared to the unaffected sites. Overall, the former iron ore mining activity has increased the biodiversity level in the Gielniowski Hump mesoregion due to an increase in the total number of species in the area, brought about by the formation of a mining-related habitat mosaic.